Promoting and Developing Seafarers’ Welfare under the Maritime Labour Convention: A Research Agenda - Progoulaki, Maria; Katradi, Aikaterini; Theotokas, Ioannis (SPOUDAI Journal of Economics and Business, 2013)
Seafarers' welfare is becoming a major issue for the international maritime community. This paper aims at examining the effect of welfare interventions onboard and ashore in the development and promotion of seafarers’ well-being. For this, it analyses the theoretical context of welfare and its aspects concerning the shipping industry. The paper is based on the results of a qualitative survey among ten Greek-owned shipping companies that manage a total fleet of more than 430 vessels. Literature review and results of the field further existing knowledge on provision of crew welfare facilities and services, as well as on the role of various stakeholders involved in the provision of such facilities. Analysis also focuses on the examination of current conditions. The paper also examines the way the Maritime Labor Convention standards are met by the industry stakeholders, discusses possible gaps that need to be filled and proposes actions for policy makers. This article introduces the research agenda in the field of welfare and well-being in the shipping industry. The present analysis contributes to our understanding on crew welfare and well-being and offers a base of dialogue on the different areas they affect. JEL Classifications: J81; I38; K31.